Impact of second wave of COVID-19 related lockdown on patients undergoing fixed orthodontic treatment in a dental teaching hospital - Poudel, Prakash; Dahal, Sirjana (Journal of Kathmandu Medical College, 2022)
Background: Lockdown due to second wave of COVID-19 was implemented, in Kathmandu from April 29, 2021. In most of the dental hospitals, patients’ regular appointments were temporarily suspended and only emergency treatments were considered. Objectives: To assess the impact of the COVID-19 related lockdown on the treatment among patients undergoing fixed orthodontic treatment. Methods: A descriptive cross-sectional study was conducted among 170 individuals undergoing fixed orthodontic treatment at Kathmandu Medical College Teaching Hospital from 1st July to 30th September 2021 after obtaining ethical approval. A standard pretested self-administered online questionnaire having questions regarding impact of COVID-19 on orthodontic treatment was sent to all the study participants. Data were entered in Microsoft Excel Sheet and analysed in Statistical Package for Social Sciences version 20. Descriptive statistics like mean, standard deviation, frequency, and percentage were calculated depending upon the nature of data. Results: Majority of the study participants (113, 66.5%) did not visit orthodontist for more than one month due to second wave of COVID-19 and were very worried (84, 49.4%) for not getting to go for regular follow-ups for their treatment. Most of them were worried thinking that their treatment time will be extended (134, 78.8%), and some (97, 57.1%) participants faced problems like broken brackets and elastics. Conclusion: This study concluded that second wave of COVID-19 had some impact on orthodontic patients. This study highlighted the importance of teledentistry for orthodontic consultation and also the need for preparing the patients to deal with orthodontic appliances if required to prevent trauma.